Pemetaan Batimetri untuk Pertimbangan Alur Pelayaran Kapal Nelayan di Pantai Sembulang, Kecamatan Galang - Rassarandi, Farouki Dinda; Chayati, Siti Noor; Sari, Luthfiya Ratna; Lubis, M Zainuddin; Gustin, Oktavianto; Ditya, Dwiki Novri; Aprilianda, Afifah; Wardani, Adelia Eky (Jurnal Geospasial Indonesia, 2020)
Sembulang is located in a strategic maritime location and supports the majority of the local population to work as fishermen. In addition, Sembulang is also directly adjacent to the waters of Mubut Island which is one of the favorite tourist attractions in Batam and also to the waters leading to Bintan and Tanjungpinang, making it a popular port for people in that location. However, until now there has not been an official sea map or cruise line map for traditional fishing boats / local transportation to support economic and tourism activities there. The flow of a cruise is very closely related to the depth of a waters. Water depth data can be used by fishermen and boat captains as a reference when they are sailing across Sembulang Beach. The purpose of this study was to analyze the bathymetry conditions in Sembulang Beach, Galang, which were used as a reference for safe and efficient ship grooves considerations. Bathymetry mapping is done by using multibeam echosounder to create a seafloor topographic map at the research location which is then analyzed based on the depth and width of the cruise line which is ideal for the specifications of traditional fishing vessels. Based on the analysis that has been done, it can be concluded that only ships with size <5 GT with the form of "V" Pump Boat, "V", "V" High Bow, "V" Katir, "V" Without Katir, "U" Katir and 5 GTs with safe "U" and "V" shapes to be anchored at Sembulang pier. In other words, traditional fishing boats with a size of GT 10 GT are not recommended to dock at the pier.